POTENSI RIMPANG KENCUR (Kaempferia galanga L.) SEBAGAI PENCEGAH OSTEOPOROSIS DAN PENURUN KOLESTEROL MELAUI STUDI IN-VIVO DAN IN-SILICO - Sri Handayani; Fera Elia; Siti Istatoah; Erika Indah; Ibrahim Arifin (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Ethyl p-methoxycinnamate and ethyl cinnamate as a phytoestrogen in galangal root (Kaempferia galanga L.) expected to be used for replacing the Hormone Replacement Therapy on prevention osteoporosis and as anti-cholesterol in menopausal women. The purpose of this study is to explore the potential estrogenic effect of galangal root extract on prevention of osteoporosis and as an anti-cholesterol agent. In-silico test is performed to measure the molecular interactions between ethyl p-methoxycinnamate and ethyl cinnamate with estrogen receptor protein (1QKM) and in-vivo tests conducted by the ovariectomy method on female Wistar rats. Thirty female Wistar rats were divided into six treatment groups. Group I is the normal mice and the group II-VI is the ovariectomies rats. Ovariectomy surgery performed at 70 days of age rats. Group II is the baseline of ovariectomized rats. Group III rats treated with CMC-Na 0.5% (control). Group IV rats are treated with estradiol 2 μg/kg BW/day while the group V and VI rats are rats treated with galangal root ethanol extract (500 and 1.000) mg/kg BW/day. Administration of the test material was performed for 30 days. At the end of the experiment, a blood sample was taken from orbital sinus for measurement of blood lipid levels. All the rats were sacrificed for necropsy procedures. The results showed that galangal root ethanol extracts significantly decrease the cholesterol and LDL levels, and enhance the femur bone density. However, extract has not significantly effect in decrease the triglyceride and enhance the HDL levels of ovariectomized rats. There were almost the same binding energy between ethyl p-methoxycinnamate, ethyl cinnamate and 17β-estradiol on 1QKM protein with binding energy is -94.9984; -949 948 and -94.9982 respectively. Key words: Kaempferia galanga L., osteoporosis and anti-cholesterol agent, in-vivo, in-silico